HUBUNGAN TINGKAT PENGETAHUAN TIM BEDAH TENTANG SURGICAL PATIENT SAFETY DENGAN KEPATUHAN DALAM PELAKSANAAN SURGICAL SAFETY CHEKLIST DI RUANG OK RSUD DUNGUS MADIUN - Ganda Ardiansyah; Prisca Dhaniar Pradesty; Henny Purwandari (LPPM STIKes SATRIA BHAKTI NGANJUK, 2025)
Patient Safety has a critical component of hospital qualitymanagement. One of the components in Patient Safety that must be implemented in theOperating Room is the Surgical Safety Checklist. Compliance in the implementation of theSurgical Safety Checklist is influenced by several factors such as knowledge of SurgicalPatient Safety owned by the Surgical Team. This study aims to determine the relationshipbetween the level of knowledge of the surgical team about Surgical Patient Safety withcompliance in the implementation of Surgical Safety Checklist in the Operating Room ofDungus Hospital Madiun.